Optimizing the Implementation of Incoterms 2020 in Support of International Trade Efficiency - Arifin, Zaenal (Innovative: Journal Of Social Science Research, 2025)
TIncoterms (International Commercial Terms) is a set of international rules compiled by the International Chamber of Commerce (ICC) to regulate the rights and obligations of parties in cross-border buying and selling contracts. This article aims to analyze the strategic role of Incoterms in international trade, examine the significant changes in Incoterms 2020, and identify the challenges of its implementation among business actors, especially in developing countries such as Indonesia. This research uses a descriptive qualitative approach with literature study techniques sourced from scientific journals, books, and ICC official documents. The results show that Incoterms provides clarity on logistics responsibilities, risks, and costs, but its implementation still faces barriers such as low legal literacy and lack of technical training in the small and medium enterprise sector. Changes in Incoterms 2020, such as the replacement of terms and adjustments to insurance coverage, demand better adaptation from businesses. This article recommends increased education, practice-based training, and synergy between government, academia, and industry players to improve understanding and implementation of Incoterms as an integral part of global trade strategies.